Phenolic Profiles of Different Apricot Varieties Grown in Spain: Discrimination Among Cultivars During the Harvest Season - Julia Morales; Helena Gómez-Martínez; Almudena Bermejo (Agronomy)
Apricot is one of the most important Mediterranean fruits with high diversity and fruit quality properties, being an excellent raw material for polyphenol compounds. This study aimed to determine the anthocyanin, quercetin glycoside and phenolic acid contents in new apricot genotypes from the breeding program at the Instituto Valenciano de Investigaciones Agrarias, confirming the potential of the ‘Goldrich’ cultivar to be a parental donor for increasing the antioxidant content, which would, in turn, enhance fruit quality. Phenolic composition of the apricot accessions is strongly genotype-dependent, with the concentrations of overall total phenolic compounds ranging from 770 to 260 mg 100 g−1 DW, reflecting significant genetic diversity. ‘Goldrich’ contributed to the polyphenol content; however, its influence varied across derived varieties, with ‘GG9310’ and ‘GG979’ enhancing the shikimic acid pathway and accumulating high levels of total phenolics. In contrast, ‘Mitger’ and ‘HG9850’ stood out for high anthocyanin synthesis, despite their lower levels of flavonols and phenolic acids. The predominant anthocyanin was cyanidin-3-O-rutinoside, followed by cyanidin-3-O-glucoside and peonidin-3-O-rutinoside in smaller amounts. Other phenolics were rutin and quercetin-3-O-glucuronide, as well as neochlorogenic and chlorogenic acids. The PCA model was applied to all data to identify the most attractive cultivars, and chromatographic analysis was performed in a short time using Ultra-High-Performance Liquid Chromatography (UHPLC) with diode array and mass spectrometric detection. Apricot peel is an excellent source of nutraceutical compounds with a chemical composition strongly determined by the cultivar. Results can help establish authenticity markers for apricot cultivars.